LED based Fourier transform absorption spectroscopy of H217O in the 14900–15600 cm−1 spectral region. (September 2020) - Vasilenko, I.A.; Naumenko, O.V.; Serdyukov, V.I.; Sinitsa, L.N.
Highlights: Positions and intensities of 661 H2 17 O spectral lines were determined for the first time in the range 14900-15600 cm −1 . A total of 285 H2 17 O rotational levels belonging to 12 vibrational states were determined for the first time. The high quality of the H2 17 O energy levels from the recent line list HotWat78 (10.1093/mnras/stw3125 ) was confirmed. Some relevant discrepancies were found between the experimental line intensities of H2 17 O absorption lines and the corresponding calculated data from the line list HotWat78 (10.1093/mnras/stw3125 ), especially for the (231) – (000) band. Abstract: The vibration-rotation absorption spectrum of 17 O-enriched water vapor in the range 14900–15600 cm −1 was recorded for the first time by a Fourier Transform Spectrometer coupled to a multi-pass White-type cell providing an optical path length of 34.8 m at room temperature with a spectral resolution of 0.05 cm −1 using high luminance LED (light emitting diode) light source. The high signal-to-noise ratio allowed for the accurate determination of 1047 positions of water lines, of which 661 lines were attributed to the H2 17 O water isotopologue. The rovibrational assignment was based on new variational calculations, which allowed retrieving 285 experimental rotational-vibrational energy levels belonging to twelve vibrational states of the H2 17 O molecule: (410), (330), (311), (231), (212), (151), (033), (052), (113), (132), (180), and (081). The 3ν1 +ν2 +ν3, 2ν1 +3ν2 +ν3 and 4ν1 +ν2 vibrational bands centered, respectively, at 15325.617, 15095.166 and 15322.533 cm −1, dominate the spectrum. A detailed comparison of the H2 17 O line intensities recorded in this study with observed literature data and with recent high-precision variational calculations showed that the calculated intensities for the (231) - (000) band are weaker by 57% than the experimental ones. The data set obtained in this study will help to improve the quality of variational calculations for water vapor.